Hydrogeochemical and isotopic signature of surface and groundwater in a highly industrialized sector of the Rio de la Plata coastal plain (Argentina). Issue 1 (15th July 2017) - Santucci, L.; Carol, E.; Borzi, G.; García, M.G.
Abstract: The coastal plain of the middle estuary of the Río de la Plata is a highly industrialized area and is densely populated by sectors. The main human activity in the sector encompassed between the cities of Ensenada and Berisso is associated with the petrochemical industry. In this work, hydrogeochemical and isotopic characteristics of surface and groundwater in the impacted area are analyzed and the results are contrasted with those obtained in an undisturbed protected area. Major and trace elements were determined using standardized methods while the stable isotopes δ 18 O y δ 2 H were analyzed by mass spectroscopy. Human impact is evidenced by the occurrence of large variations in the major chemical composition of water, and also by the elevated concentrations of some trace elements that are not contributed from natural sources. These results may contribute to the understanding of chemical processes and pollutants distribution in highly industrialized coastal plain areas. Highlights: Hydrochemistry of natural and industrialized areas in the coastal of Río de la Plata Isotopes, major and minor ions were analyzed to assess water quality. In the petrochemical pole hydrochemistry variations occur due to contamination. In natural areas groundwater chemistry is influenced by the Río de la Plata.